RanCoord — A random geographic coordinates generator for transport and logistics research and development activities[Formula presented] - Carvalho, Hugo Silva (2022)
RanCoord is an open-source Python package that allows to easily generate random coordinates within a set of geographic boundaries. The framework offers methods to generate, save and plot a determined number of random coordinates generated from a location polygon or a simple name/address through its geocoding. Such geographic methods are well-suited for research and development activities in transport and logistics, such as the Travel Salesman Problem (TSP) and the Vehicle Routing Problem (VRP).